2017
DOI: 10.1186/s12915-017-0368-4
|View full text |Cite
|
Sign up to set email alerts
|

Single swim sessions in C. elegans induce key features of mammalian exercise

Abstract: BackgroundExercise exerts remarkably powerful effects on metabolism and health, with anti-disease and anti-aging outcomes. Pharmacological manipulation of exercise benefit circuits might improve the health of the sedentary and the aging populations. Still, how exercised muscle signals to induce system-wide health improvement remains poorly understood. With a long-term interest in interventions that promote animal-wide health improvement, we sought to define exercise options for Caenorhabditis elegans.ResultsHe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(135 citation statements)
references
References 77 publications
(81 reference statements)
7
125
2
1
Order By: Relevance
“…Our previous analysis of single swim sessions supported that swimming is an endurance-like exercise for C. elegans [15]. In mammals, long-term endurance exercise leads to profound transcriptional changes at the muscle level, with upregulation of muscle structural genes as one of the reproducible changes [23][24][25].…”
Section: Multiple Daily Swim Sessions Are Essential For C Elegans Exmentioning
confidence: 68%
See 1 more Smart Citation
“…Our previous analysis of single swim sessions supported that swimming is an endurance-like exercise for C. elegans [15]. In mammals, long-term endurance exercise leads to profound transcriptional changes at the muscle level, with upregulation of muscle structural genes as one of the reproducible changes [23][24][25].…”
Section: Multiple Daily Swim Sessions Are Essential For C Elegans Exmentioning
confidence: 68%
“…We have shown previously that swimming in a liquid environment is more energetically demanding for C. elegans than the crawling motion on agar plates used in standard lab growth protocols [15]. Moreover, we showed that a single 90 min C. elegans swim session induces key features of mammalian exercise, namely locomotory fatigue, muscle mitochondrial oxidation, a transcriptional oxidative stress response, and changes in carbohydrate and fat metabolism [15].…”
Section: Introductionmentioning
confidence: 92%
“…The animals were washed from their culture plates with chemotaxis buffer (5 mM potassium phosphate, 1 mM calcium chloride, 1 mM magnesium sulfate) until they were free of bacteria. The total time that the worms spent swimming in liquid was kept under 30 minutes to minimize fatigue [57]. Then, 5 μL of the solution containing animals was added onto the center.…”
Section: D Chemotaxis Assaysmentioning
confidence: 99%
“…RNA extraction and quantitative PCR were carried out as previously described [57]. Briefly, we collected N2 C. elegans after burrowing (~30 animals per sample) into TRIzol Reagent (Ambion) and immediately froze animals in liquid nitrogen.…”
Section: Rna Extraction and Quantitative Pcrmentioning
confidence: 99%
“…Superoxide dismutases are responsible for converting superoxide radicals to H2O2. We tested both cytosolic superoxide dismutases, SOD-1 and SOD-5, for effects on spermathecal transit times (Blaise et al, 2009;Braeckman et al, 2016;Doonan et al, 2008;Laranjeiro et al, 2017). DIC timelapse microscopy of ovulations revealed that mutation of sod-1, but not sod-5, resulted in shorter dwell times and no change in exit time compared to wild type (Figure 4 A,B).…”
Section: Sod-1 Regulates the Redox Environment Of The Spermathecamentioning
confidence: 99%